How ‘hot’ is too hot? Evaluating acceptable outdoor thermal comfort ranges in an equatorial urban park - HENG, Su Li (Institutional Knowledge at Singapore Management University, 2019)
Urban green spaces offer vital ecosystem services such as regulating elevated temperatures in cities. Less information exists, however, on how urban green spaces influence outdoor thermal comfort (OTC), which is dependent on people’s perceptions of the complex interactions amongst ambient humidity, wind and both air and radiant temperatures. In this study, we analysed an existing OTC dataset compiled within a large Singapore urban park and calibrated OTC thresholds for physiological equivalent temperatures (PET) by analysing PET against thermal perception survey responses from the park visitors (n = 1508). We examined OTC according to (i) neutral, (ii) acceptable and (iii) preferred temperatures, where respondents felt ‘comfortable’ outdoors in the park. We estimated that neutral temperature, when all respondents experience neither heat nor cold stress, is 26.2 °C; acceptable temperatures, when only slight heat or cold stress is experienced, range between 21.6 and 31.6 °C; and preferred (‘ideal’) temperature for all respondents is 24.2 °C. Respondents residing for more than 6 months in Singapore achieved thermal neutrality, suggesting that a greater degree of thermal adaptation likely developed during acclimatisation to local climate through a combination of physiological, behavioural and psychological circumstances. Comparisons with other OTC studies showed differences in synoptic climates are linked to variations in the magnitude and ranges of perceived PET. Lastly, respondents in this study perceived lower neutral and preferred temperatures compared to respondents surveyed over a variety of urban land use categories in another local study. The differences in neutral and preferred temperatures between studies suggest that lower park temperatures and different environmental attitudes influence perceived OTC.